2023
DOI: 10.1088/1402-4896/aca6b5
|View full text |Cite
|
Sign up to set email alerts
|

Calculation and analysis the dynamic breakdown characteristic of SF6 discharge caused by GIS disconnector operation

Abstract: In order to accurately calculate the very fast transient overvoltage(VFTO),it is very important and necessary to carry out the study on breakdown characteristic of SF6 gas discharge and get the expression of critical breakdown voltage during GIS disconnector operation. Therefore, a study of dynamic breakdown characteristic of SF6 discharge caused by GIS disconnector operation is conducted. For gas discharge modeling, considering the micro discharge process will lead to the problems of complex modeling and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…We employ the DMol module in the Materials Studio (MS) to perform geometry optimization on the Pd-MoTe 2 monolayer, thereby ensuring the model structure’s stability. First, a 4*4*1 MoTe 2 monolayer supercell is established, which contains 16 Mo atoms and 32 Te atoms .…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…We employ the DMol module in the Materials Studio (MS) to perform geometry optimization on the Pd-MoTe 2 monolayer, thereby ensuring the model structure’s stability. First, a 4*4*1 MoTe 2 monolayer supercell is established, which contains 16 Mo atoms and 32 Te atoms .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Due to its excellent insulation and arc extinguishing properties, SF 6 is widely used in high-voltage equipment and gas insulation systems. However, during long-term operation, SF 6 will inevitably decompose into a series of low-fluoride sulfides due to partial discharge caused by unavoidable insulation defects within the equipment. These byproducts react quickly with micro-oxygen and microwater in the gas insulation system, generating a series of relatively stable chemical components, including SO 2 , SOF 2 , H 2 S, SO 2 F 2 , HF, etc. If not properly handled, they not only pose a risk to human health but also corrode the insulation system, exacerbate discharges, and affect the stability of system operation .…”
Section: Introductionmentioning
confidence: 99%
“…Keeping the temperature of the busbar lower is one way to cut down on power losses in GIS systems and lower overall energy consumption. A magnetic-thermal coupling finite element methodology was proposed as a method for predicting the growth in busbar temperature (3). Experiments have shown that this method, which generates heat in the busbar by relying on the loss detected in the magnetic field analysis, is effective.…”
Section: Introductionmentioning
confidence: 99%